Current trends in acute leukemia: A cross-sectional survey of adult acute leukemia cases - Bhutto, Sorath; Haider, Ghulam; Hashmat, Sana; Alam, Nargis; Zahoor, Saima; Qazi, Shayan Ali; Qureshi, Areeba (LIAQUAT MEDICAL RESEARCH JOURNAL, 2025)
Acute Leukemia (AL) is one of the cancer on rise globally, there is dearth of regional information in particular gender pattern of the disease among adult population from Pakistan. Therefore, this cross-sectional study was designed and conducted at Medical Oncology department at Jinnah Postgraduate Medical Center (JPMC), Karachi, Pakistan. The said department receives cancer patients all over from the province of Sindh as well as other provinces. A total of 130 adult patients presenting at Oncology OPD with diagnosis of acute leukemia and included in this study. Participants were selected using non-probability convenient sampling technique. Data was collected using a structured questionnaire and analyzed using SPSS version 24.0. The median age of male AL patients was significantly higher as compared to female AL patients i.e. 30 years ; IQR =18 versus 24 years; IQR=21.25 years (p-value= <0.05). The study found male: female ratio of AL was 1.8:1. No statistically significant differences were observed in the socio-demographic and disease-related characteristics among male and female AL patients. The current study concludes that acute leukemias has male predominance whereas the average age of presentation was comparatively lower among females as compared to males.